Performance of Dye Sensitized Solar Cells (DSSCs) with ZnO Nanorod Electrode in Different Seed Solution - Herlin Pujiarti; Nadiya Ayu Astarini; Markus Diantoro; Muhammad Safwan Aziz; Rachmat Hidayat (Universitas Negeri Malang, 2021)
Studies of comparing the performance of photoelectrode for dye-sensitized solar cells (DSSCs) continue to be carried out and developed. The ZnO nanorods as an electrode for DSSCs have been shown to have high electron collection due to the capability of electron photoexcitation and increased electron transport. Various methods of making ZnO nanorods have been studied and developed. However, the method requires controlled conditions under high temperature and pressure, thus limiting the commercialization of ZnO nanorods. Therefore, the seed solution-based hydrothermal method was chosen in the ZnO nanorod deposition process because it is an effective method, low-cost and easier fabrication process. The method of growing ZnO nanorod was carried out with three times of growing for 6 hours. ZnO nanorod was synthesized using different seed solutions, namely sample 1 and sample 2 by using methoxy and isopropanol, respectively. In this work, the SEM image shows the growth of ZnO nanorods vertically aligned on the FTO substrate and resulted in a smaller diameter for the isopropanol seed solution. The smaller diameter of the ZnO nanorod provides a larger surface area then increasing the total amount of dye attached to the ZnO nanorod and improve the photovoltaic performance.DOI: 10.17977/um024v6i22021p077